Balancing Profit and Planet: The Impact of Green Marketing on Brand Performance - Rofiq, Ainur; Amanda, Gia (Jurnal Kewirausahaan dan Inovasi, 2025)
Purpose – The growing consumer awareness of environmental issues has driven companies to adopt more environmentally responsible business strategies. This research aims to describe the implementation of green marketing strategies by Curcuma Plus, a well-known children’s multivitamin brand, and assess their impact on the brand’s sustainability.  Design/methodology/approach – The data for this qualitative descriptive study were collected through interviews, observations, and document analysis.      Findings – The findings indicate that Curcuma Plus has achieved a "greener" status by balancing business interests with environmental commitments through a "shaded green" approach. Although the green market segment remains relatively small, Curcuma Plus has successfully differentiated itself by enhancing its green attributes, notably its high-quality products. Furthermore, green initiatives have been incorporated into the four elements of the marketing mix. That are product, price, place, and promotion. Despite the ongoing challenges, implementing these strategies enabled the brand to strengthened its market position and added value, reflected in improved consumer loyalty, enhanced brand image, and expanded market share. This research provides practical insight for companies to adopt comprehensive green marketing strategies. Originality/value – This study offers original insight into the application of green marketing strategies within the children’s multivitamin industry, a relatively underexplored sector. By highlighting the “shaded green” approach and its integration into the four elements of the marketing mix, this research demonstrates how environmental commitment can enhance brand sustainability and competitive advantage.